Global analysis of influenza epidemic characteristics in the first two seasons after lifting the nonpharmaceutical interventions for COVID-19 - Xiaowei Chen; Honghong Chen; Fangfang Tao; Yinzi Chen; Ying Zhou; Jian Cheng; Xiling Wang (International Journal of Infectious Diseases)
Objectives: The COVID-19 pandemic significantly disrupted the global influenza seasonal patterns due to nonpharmaceutical interventions. This study aims to describe the influenza seasonal characteristics in the first two seasons after lifting COVID-19 NPIs and assess shifts before, during, and after the pandemic. Methods: We analyzed country-specific weekly influenza data (2011-2024) from WHO FluNet and collected COVID-19 NPI timing from official announcements. The study was divided into pre-pandemic, pandemic, and post-pandemic phases, estimating epidemic onset, peak week, peak intensity, and duration by climate zones. Results: In temperate countries, peak intensity after the pandemic decreased by 8.4 %, while duration increased by 1.8 weeks, and onset and peak were delayed by 18.5 and 22.8 weeks compared to regular seasonal pattern before the pandemic. Subtropical countries experienced a 17.2 % decrease in peak intensity, a 2.4-week decrease in duration, and delays in onset and peak by 13.5 and 2.3 weeks. Tropical countries had a 10 % decrease in peak intensity, a 3-week reduction in duration, and a 6.6-week delay in onset with no significant change in peak time. Conclusion: Influenza seasonality shifted significantly after the pandemic, with epidemic durations returning to typical patterns but peak intensities remained low. Robust surveillance after an infectious disease pandemic is crucial to inform prevention and control strategies.